Evaluation of effectiveness and improvement factors of occupational health and safety management system in the Republic of Korea Navy based on AHP-entropy and IPA. - Sang Ji Lee; Yun-Hee Choi; Da-An Huh; Seok Joon Yoon; Kyong Whan Moon (PLoS ONE, 2023)
The Republic of Korea Navy (ROKN) has applied Occupational Health and Safety Management System (OHSMS), but the effectiveness of OHSMS is being questioned due to continuous industrial accidents that continue to occur. Although OHSMS, which has been generally applied in enterprises, has more potential for improper implementation in the military, there are few studies on OHSMS in the military. Therefore, this study verified the effectiveness of OHSMS in the ROKN and derived improvement factors. This study was conducted in a two-step process. First, we surveyed 629 workers at the ROKN workplaces to confirm the effectiveness of OHSMS by comparing occupational health and safety (OHS) efforts according to whether OHSMS was applied and the period of application. Second, 29 naval OHSMS experts evaluated the factors for improving OHSMS using two decision-making tools: Analytic Hierarchy Process (AHP)-entropy and Importance-Performance Analysis (IPA). The study results indicate that the OHS efforts of OHSMS-applied workplaces were similar to that of unapplied. Also, no better OHS efforts were identified in workplaces with more extended OHSMS application periods. There were five improvement factors of OHSMS applied to the ROKN workplaces, with the highest weight in the following order: consultation and participation of workers; resources; competence; hazard identification and risk assessment; and organizational roles, responsibilities, and authorities. The effectiveness of OHSMS in the ROKN was insufficient. Therefore, the ROKN needs focused improvement efforts on the five requirements to implement OHSMS practically. These results can be helpful information for the ROKN to apply OHSMS more effectively for industrial safety.